Sosialisasi Mengenai Program BPJS Ketenagakerjaan Dengan Tujuan Meningkatkan Keasadaran Diri di kalangan Mahasiswa Kota Surabaya - Davina Ayu Fakhriyyah; Lia Nirawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
National social security exists with the aim of improving the welfare of the Indonesian people. BPJS Employment acts as a Social Security organizing institution in Indonesia with the aim of protecting workers, meeting their basic needs and providing certainty of family income. Although the benefits provided are very significant, the lack of public understanding can lead to misunderstandings and make some people reluctant to take part even though the benefits are quite large. Despite the general awareness of the importance of BPJS employment protection, many students still lack understanding of BPJS Employment. It is important for students who are preparing to enter the workforce to understand the importance of employment protection. To improve students' understanding of the importance of BPJS Employment, effective socialization strategies need to be promoted through lectures and discussions. The purpose of this research is to improve students' understanding of the importance of BPJS through discussion socialization, The results showed that this socialization program succeeded in increasing students' understanding of the benefits and security of BPJS Employment through interactive discussions between participants and speakers.